Wytyczne dotyczące postępowania w przypadku zeza u dzieci - Loba, Piotr; Gotz-Więckowska, Anna; Hautz, Wojciech; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
The treatment of strabismus is an area of ophthalmology which is overshadowed by other more common eye conditions. Consequently, a lot of controversy and misunderstanding still surrounds the issue. With a view to improving the standards of ophthalmic care for young patients, the Section of Pediatric Ophthalmology and Strabismus Treatment of the Polish Ophthalmological Society presents guidelines and recommendations on the basic principles of strabismus management in children.